Processing and interpretation of 3D seismic data of an oil field in central of Iraq using AVO techniques - S. Al Mukhtar, Khalid; A. Alsayadi, Anwar A. (Iraqi Journal of Science, 2023)
In this research, a qualitative seismic processing and interpretation is made upthrough using 3D-seismic reflection data of East-Baghdad oil field in the central partof Iraq. We used the new technique, this technique is used for the direct hydrocarbonsindicators (DHI) called Amplitude Versus Offset or Angle (AVO or AVA) technique.For this purposes a cube of 3D seismic data (Pre-stack) was chosen in addition to theavailable data of wells Z-2 and Z-24. These data were processed and interpreted byutilizing the programs of the HRS-9* software where we have studied and analyzedthe AVO within Zubair Formation. Many AVO processing operations were carriedout which include AVO processing (Pre-conditioning for gathers), AVO modelingand AVO analysis. Analyzing these variations in amplitude within offset or with angle(AVA), reveals the identification of one type of reservoir which is related to the fluidcontents and lithology.